History and Memory as Factors in Greek Orthodox Pilgrimage to the Holy Land under Crusader Rule - Jotischky, Andrew (Studies in church history, 2000)
Western pilgrimage to the Holy Land can be explained through patterns of evolving spirituality. The development in the eleventh century of a penitential theology in which pilgrimage played a crucial role, coupled with the practical opportunities for travel occasioned by the success of the First Crusade, brought the Holy Land closer than ever. The survival of a strong textual tradition manifested in pilgrimage itineraries, many of which are autobiographical in tone, further contributes to our perception of pilgrimage as an example of medieval religion in practice.